2015
DOI: 10.2991/iceb-15.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Ageing Population on Healthcare Expenditure: A Comparative Study of China and India

Abstract: The motivation of the study is to compare the impact of aging population on healthcare expenditure between China and India as demographic projection forecast that the percentage people above 65 years will be 26 percent by 2050. The used of long time series data of China and India from 1970 to 2011 helps us to identify the long run relationship between ageing population and healthcare expenditure using ARDL bound testing approach. The result of the bounds test showed that there is a stable, long-run relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The results of long-run estimates of ARDL suggest that population aging has a statistically positive and significant impact on per capita health expenditure which implies that an increase in the aged percentage of the population in the country requires more healthrelated problems and hence health expenditures in the economy increases. This research finding is supported by various studies in the literature and specifically by Nordin et al (2017) who have found the long-run relationship between population aging and HCE for India and China using a similar approach.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results of long-run estimates of ARDL suggest that population aging has a statistically positive and significant impact on per capita health expenditure which implies that an increase in the aged percentage of the population in the country requires more healthrelated problems and hence health expenditures in the economy increases. This research finding is supported by various studies in the literature and specifically by Nordin et al (2017) who have found the long-run relationship between population aging and HCE for India and China using a similar approach.…”
Section: Resultssupporting
confidence: 83%
“…The authors found that the elderly population positively affects the HCE per capita. Nordin et al (2017) in their study compared the relationship between population aging and HCE between India and China. Using the autoregressive distributed lag (ARDL) approach, the study found a positive long-run relationship between population aging and HCE.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…46 Our results are similar to literature that show ageing most likely influences growth in health expenditures. [47][48][49] Lopreite and Mauro 48 show the impact of demographic changes on healthcare expenditure in the case study of Italy. The study indicates that increasing population over the age of 65 lead to higher incidence of chronic disease and consequent impact of healthcare spending.…”
Section: Notementioning
confidence: 99%
“…The age effect of healthcare expenditure for the population aged 65 or over was the most significant among the different age groups as healthcare expenditure per capita of the age group 65 years or over is 7.25 times as much as the population aged <25 years. However, Nordin et al 49 argued that in the case of China the ageing population is a more dominant influence on healthcare expenditures because the total ageing in China is greater than that of the population in India.…”
Section: Notementioning
confidence: 99%
“…Changes in prices of goods and services which are exchanged in the normal market can be associated with consumer behaviour. [ 25 ] asks that in cases with no observable markets, how do you express utility such as the benefits of higher education, or protection of the environment, healthcare, or standard of living? According to Ref.…”
Section: Introductionmentioning
confidence: 99%